Throughput Analysis in a Wireless Powered Mobile Communication System - Petros S. Bithas (IEEE, 2021)
In this paper, important statistical characteristics of the ratio of double generalized-gamma random variables have been analytically evaluated. The derived results have been applied in a wireless powered mobile-to-mobile communication scenario, which operates in the presence of interference. The performance is investigated using the throughput criterion under two different scenarios, namely delay limited and delay tolerant transmissions. Moreover, since the links’ reliability depends on the mobile nodes locations, the $2D$ Poisson point process is employed in order to more realistically model the physical layer behavior. The analytical results provided generalize previously reported ones, while the numerical results presented reveal the impact of various system’s and channel’s parameters, e.g., distance among nodes, interference, the non-linearity of the wireless medium.